2019
DOI: 10.3390/electronics8111254
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Non-Orthogonal Multiple Access over Log-Normal Power Line Communication Channels

Abstract: In this paper, we analyze the performance of cooperative power domain non-orthogonal multiple access (NOMA) in power line communication (PLC) networks. Due to the high signal attenuation of the source to user links, a relay aids communication from the source to two users. With half-duplex transmission, the source transmits a superimposed symbol in the first phase. The relay utilizes amplify-and-forward (AF) and decode-and-forward (DF) protocol on the received superimposed signal and forwards it to the users in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Hence, the adaptive scheme proposed in [18] showed enhanced throughput performance when compared to both the TDMA and conventional cooperative NOMA schemes. A comparative study of AF and DF protocols for one-way relayaided NOMA scheme in PLC networks was considered in [19]. Based on the results, it was shown that while DF relaying performs better than AF relaying in good fading scenarios, the two relaying protocols achieve similar performance in bad fading scenarios.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, the adaptive scheme proposed in [18] showed enhanced throughput performance when compared to both the TDMA and conventional cooperative NOMA schemes. A comparative study of AF and DF protocols for one-way relayaided NOMA scheme in PLC networks was considered in [19]. Based on the results, it was shown that while DF relaying performs better than AF relaying in good fading scenarios, the two relaying protocols achieve similar performance in bad fading scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned works [16]- [19] focused on one-way relaying under the assumption of perfect SIC. However, perfect SIC is difficult to achieve in practice due to imperfect signal decoding, synchronization, imperfect channel state information (CSI), and high signal attenuation issues [21], [22].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations